Fourier Transform Infrared Spectroscopy Analysis Of Oil Of Menthaarvensis Grown At Sites Varying With Vehicular Traffic Loads In Lucknow City, India - Prakash, Nidhi; Yumus, Mohhamad (International Journal of Environment, 2013)
The demand of the essential oil of mint species; widely used in food, pharmaceutical and cosmetic industries, is growing throughout the world. Owing its significance, it was felt important to know the changes in chemical characteristics of the oil, if any, for economic value when the crop of Mentha is grown near highways, railway tracks or areas having heavy traffic loads. To assess the effect of vehicular emissions on menthol (mint oil), transfer experiment study was conducted. Firstly, within the municipal premises of Lucknow city, five sites (Road stretches) were identified based on survey of Lucknow city and the available data on air pollution loads. Sites were selected which were differing from each other significantly in terms of the number of vehicles (source of pollution) plying on them but were quite similar to each other in other eco-physiological factors. On the select sites equal number of potted Menthaarvensis plants of the same age, height and vigour of saccham variety obtained from CSIR-CIMAP was kept to get exposed to auto-exhaust pollutants for one year. Irrigation regime at all sites was kept uniform to avoid the influence of any other variable other than vehicular emissions. An analysis of hydro-distillated essential oil of Menthaarvensis variety Sascham under FTIR (Fourier Transform Infrared Spectroscopy) revealed some qualitative changes in the organic-compounds of the oil from plants grown at sites of Lucknow city loaded with high vehicular load (auto-exhaust pollutants) over plants kept under relatively pollution free site. Several indicator bands that are pertained to functional groups represent chemical components or metabolic products. The quantity of the peppermint oil extracted from plants of site having highest traffic loads, in turn maximum ambient pollutants (NO2, SO2, O3, SPM & RSPM) was also found less as compared to plants grown in less polluted site. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 16-25 DOI: http://dx.doi.org/10.3126/ije.v2i1.9204